Plasticity-Related PKMζ Signaling in the Insular Cortex Is Involved in the Modulation of Neuropathic Pain after Nerve Injury. (20th September 2015) - Han, Jeongsoo; Kwon, Minjee; Cha, Myeounghoon; Tanioka, Motomasa; Hong, Seong-Karp; Bai, Sun Joon; Lee, Bae Hwan
Abstract : The insular cortex (IC) is associated with important functions linked with pain and emotions. According to recent reports, neural plasticity in the brain including the IC can be induced by nerve injury and may contribute to chronic pain. Continuous active kinase, protein kinase M ζ (PKM ζ ), has been known to maintain the long-term potentiation. This study was conducted to determine the role of PKM ζ in the IC, which may be involved in the modulation of neuropathic pain. Mechanical allodynia test and immunohistochemistry (IHC) of zif268, an activity-dependent transcription factor required for neuronal plasticity, were performed after nerve injury. After ζ -pseudosubstrate inhibitory peptide (ZIP, a selective inhibitor of PKM ζ ) injection, mechanical allodynia test and immunoblotting of PKM ζ, phospho-PKM ζ (p-PKM ζ ), and GluR1 and GluR2 were observed. IHC demonstrated that zif268 expression significantly increased in the IC after nerve injury. Mechanical allodynia was significantly decreased by ZIP microinjection into the IC. The analgesic effect lasted for 12 hours. Moreover, the levels of GluR1, GluR2, and p-PKM ζ were decreased after ZIP microinjection. These results suggest that peripheral nerve injury induces neural plasticity related to PKM ζ and that ZIP has potential applications for relieving chronic pain.